Media Monitoring Analysis of Government Image in Infrastructure Development in Indonesia - Hutagalung, Simon Sumanjoyo; Kartika, Tina; Suciska, Wulan (Jurnal Komunikasi, 2023)
The massive infrastructure development program during president Jokowi's administration will always produce a variety of different perceptions in the public area. Public perception will be built differently and form the image of the government in the scope of the implementation of the program and can be the material of preparing a government communication plan to the public. Research objectives in this article; Analyze the dynamics of the government's image in the topic of infrastructure development on social and non-media sosial. More specifically, several points of purpose are to be achieved as follows: (a). The amount of discussion volume on the topic of infrastructure development, (b). The dominant parties discuss and respond to the topic of infrastructure development, (c). Dynamics of public sentiment in discussions with the topic of infrastructure development. The research method is done with media monitoring analysis that starts with a search profile and searches for terms or keywords. Furthermore, data mining using the Brand24 Media Monitoring application using the keywords Infrastructure Development and Infrastructure Projects. The data mining process is carried out in a span of 90 days, from Aug 16, 2021 to Nov 14, 2021. Data analysis is done simultaneously with the Brand24 and Microsoft Excel applications for data rechecking and confirmation of the data to be analyzed. The results of the analysis concluded; On the topic of infrastructure development, the volume of mentions was obtained by 13 thousand times, of which the most dominant media was non-media sosial with the composition of news agencies (5433) and the web (4435), while the media sosial area represented by several applications, forums, blogs, videos youtube) and podcasts had a smaller portion of the topic.